2015
DOI: 10.1016/j.juro.2014.08.088
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-Term Efficacy of Desmopressin Lyophilisate and Enuretic Alarm for Monosymptomatic Enuresis and Assessment of Predictive Factors for Success: A Randomized Prospective Trial

Abstract: In compliant patients desmopressin lyophilisate and enuretic alarm provided equivalent success at the end of treatment and after extended followup. Alarm therapy had a high rate of early withdrawal from therapy and consequently lower rates of success on intention to treat analyses. Severe enuresis (more than 5 wet nights weekly) is an important predictive factor for cure after first-line treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 11 publications
2
27
0
1
Order By: Relevance
“…Önol et al . showed that NE severity is an independent predictor of CR . In the present study, on multivariate analysis of data from patients who completed treatment, NE frequency was an independent risk factor for predicting CR (OR, 2.111; 95%CI: 1.316–3.387).…”
Section: Discussionsupporting
confidence: 49%
“…Önol et al . showed that NE severity is an independent predictor of CR . In the present study, on multivariate analysis of data from patients who completed treatment, NE frequency was an independent risk factor for predicting CR (OR, 2.111; 95%CI: 1.316–3.387).…”
Section: Discussionsupporting
confidence: 49%
“…Reported response rates vary, only 41% of patients achieved ≥ 50% reduction in wet nights in the study by Lottman et al (5), but 77% achieved > 90% reduction in the study by Onol et al (6). It depends on the type of patients selected, suboptimal adherence rates, administration methods and doses and formulations used (7).…”
Section: Discussionmentioning
confidence: 97%
“…The alarm’s mechanism of effect is not fully understood, but an increase in bladder storage capacities is reported with its use [15, 16]. Despite good efficacy when used appropriately and consistently, alarm treatment can present a significant burden to the family, and discontinuation rates are high [17]. …”
Section: Mne and Its Pathophysiologymentioning
confidence: 99%
“…Reported response rates vary (e.g. only 41 % of patients achieved ≥50 % reduction in wet nights in the study by Lottman et al [22], but 77 % achieved >90 % reduction in the study by Onol and colleagues [17]), likely affected by the type of patients selected, suboptimal adherence rates, administration methods and doses and formulations used. In general, it is estimated that around 30 % of children with enuresis are full responders to desmopressin and that 40 % have a partial response to this AVP analogue [2].…”
Section: Desmopressin Profilementioning
confidence: 99%